The mandate of dignity : Ronald Dworkin, revolutionary constitutionalism, and the claims of justice - Cornell, Drucilla; Friedman, Nick, 1984- (Just ideas., 2016)
This is the first book to review Ronald Dworkin's entire body of work in its relevance to constitutional dispensations in the Global South.